Neck circumference and waist circumference as a tool for evaluating obesity - Jindal, Mohit; Masand, Rupesh; Nimawat, Amit Kumar; Natani, Bhagwan Sahai; Verma, Chaman Ram (Indian Journal of Child Health, 2020)
Background: Obesity has acquired an epidemic proportion, leading to increased morbidity and mortality. Early identification and timely intervention in children are the need of the hour. Objective: The objective of the study was to measure and compare the neck circumference (NC) and waist circumference (WC) in normal, overweight, and obese children followed by their correlation with body mass index (BMI). Materials and Methods: This cross-sectional study was conducted in 1000 school-going children of 6–14 years age group. Their BMI, NC, and WC were measured, compared, and correlated by appropriate statistical analysis. Results: The difference between NC and WC of overweight and obese children and that of normal children was statistically significant and the measurements correlated with the BMI. The age-wise cutoff values of NC and WC in male and female children were calculated along with their sensitivity and specificity for detecting obesity. Conclusion: NC and WC are practical, efficient, and cost-effective tools to identify obesity amongst school-going children.